Effect of fluoride solutions on color and surface roughness of dental composites (Revista da Faculdade de Odontologia - UPF, 2014)
Objective: The aim of this study was to assess the ac- tion of fluoride solutions on color stability (âˆ†E) and surface roughness (Ra) of composites (Heliomolar, 4 SeasonsTM, Tetric N-CeramTM, SR AdoroTM). Materials and method: A Teflon matrix (12x2 mm) was used to fabricate 24 test specimens for each composite. The samples were separated into 4 groups (n=6), according to the immersion solution: distilled water (control), acidulated phosphate fluoride (1.23%), neutral sodium fluoride gel (2%), and solution of sodium fluoride (0.05%). Color (Spectrophotometer PCB 6807) and roughness (Surf- corder SE 1700) readings were performed before and after immersion into the solutions. Results: Composites presented color alteration within clinically acceptable limits (Î”E0.2 µm). Conclusions: Color and surface roughness alteration of the different composites was clinically acceptable after immersion in all fluoride solutions and in all periods.Keywords: Composite resins. Color. Surface properties. Acidulated phosphate fluoride.